Wounded writers ask : Am I Doing it Write? - Leigh, S. Rebecca (SensePublishers Imprint: SensePublishers, 2014)
This book addresses (and aims to dismantle) writer woundedness, a state of being that prevents students from trusting themselves as capable of writing something they can feel good about. Wounded Writers Ask: Am I Doing it Write? invites students to begin a new writing history through a collection of 48 free-writes that explore list writing, aesthetic writing, word craft, and writing that delves into personal life stories. These free-writes are invitations to develop a lead or improve a story title, to discover a character's name or replace one word for another that is more vivid, to locate a story idea or revise a story's focus. More than this, Wounded Writers Ask: Am I Doing it Write? emphasizes creative consciousness over correctness, where writing is a vehicle for exploring identity and (re)claiming voice across multiple grade levels. This book is for the wounded student writer as much as it is for the wounded classroom teacher as writer, who may feel burdened by his/her own writing history such that he/she struggles with where or how to start. For each free-write, Leigh offers Before Writing, During Writing, and After Writing suggestions with samples of student writing to guide teachers into writing engagements with their students that break down walls and open up new vistas.